ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI PEMAHAMAN MASYARAKAT MENGENAI FATWA MAJELIS ULAMA INDONESIA NOMOR 116/DSN-MUI/XI/2017 TENTANG UANG ELEKTRONIK SYARIAH DI KECAMATAN CIBUNGBULANG, KABUPATEN BOGOR. - Sriyani, Meisa; Suryani, Ermi; Putra, Bayu Purnama (Sahid Business Journal : Jurnal Penelitian Manajemen Bisnis Syariah: Program Studi Manajemen Bisnis Syariah, 2023)
This study aims to analyze the factors of education level, media access to information and religiosity that affect public understanding of MUI Fatwa No. 116/DSN-MUI/XI/2017 concerning Sharia Electronic Money. This type of research is quantitative research and the data collection method uses primary data obtained through questionnaires. The sample taken was 75 respondents using the technique of Tabachic & Fidel, in determining the sample using purposive sampling technique. data analysis method using multiple linear regression, classical assumption test and hypothesis testing (t test and f test). The results of the t-test showed that each independent variable, namely media access to information and religiosity, had no significant effect, while the level of education had a positive and significant effect with a coefficient value of 0.399 with a significant value of 0.002. The results of the f test show that there is a simultaneous positive effect between the variables of education level, access to information media and religiosity on Public Understanding of MUI Fatwa No. 116/DSN-MUI/XI/2017 Regarding Sharia Electronic Money, it can be seen that the value of Fcount > Ftable 11.616 > 2.73 with a significance level of 0.000. and it can be seen from the R Square coefficient value is 32.9% and the remaining 67.1% is explained by other reasons outside the research variable X. from the regression model, it can be seen that the level of education is the most dominant factor influencing Public Understanding of the MUI Fatwa No. 116/DSN- MUI/XI/2017 concerning Sharia Electronic Money.